Increasing Students’ Listening Mastery by Using Songs at SMA Nurul Hasanah Ciheulang - Ikawati, Dian (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2023)
This study investigates students’ listening skill by using English songs. It is known that English is taught ranging from elementary school until universities, but although English is taught in those educational level not all the students can communicate in this language. The purpose of this study to know effectiveness of using English songs to improve students listening skills because listening is the most frequent type of communication activities, listening, then, is one of the skills that need to be developed in order that the students are truly effective in understanding English. The writer tried to observe the effectiveness of songs used as the instructional media to teach students in order to have English proficiency better. The target of this research was the students at eleventh grade of SMA Nurul Hasanah Cheulang Kecamatan Rangkasbitung Lebak-Banten. There were 52 students. The hypothesis of the research is there is a positive effect of the songs used in teaching learning process on the listening achievement, or there isn't increase students listening mastery by using songs in teaching learning process. If there is found effect of songs, how effective the using songs. The data needed to answer the research question are collected by mean of test. The test is divided into pre-test on experimental group. The data were then analyzed by using t-test. Based on data analyzed, it is found that t-observe is higher than t-table (8.125>2.02). Thus, the writer has conclusion that songs can increase the students listening mastery